Rewrite the following in the form log(c).

`\log(`

`A`) + \log(`B`)

`C`

Use the rule: `\log(a) + \log(b) = \log(a \cdot b)`

.

`\log(`

`A`) + \log(`B`) = \log(`A` \cdot `B`)

`= \log(`

`C`)

Rewrite in the form log(c).

`\log(`

`C`) - \log(`A`)

`B`

Use the rule: `\log(a) - \log(b) = \log(\frac{a}{b})`

.

`\log(`

`C`) - \log(`A`) = \log(\frac{`C`}{`A`})

`= \log( `

`B` )

Rewrite in the form log(c).

`A`\log(`B`)

`pow( B, A )`

Use the rule: `n \cdot \log(a) = \log(a^{n})`

.

`A`\log(`B`) = \log(`B`^{`A`})

`= \log(`

`pow( B, A )`)